2012
DOI: 10.1080/10481885.2012.666147
|View full text |Cite
|
Sign up to set email alerts
|

On the Origins of Disorganized Attachment and Internal Working Models: Paper I. A Dyadic Systems Approach

Abstract: Despite important recent progress in understanding disorganized attachment, we still lack a full understanding of the mechanisms of disorganized attachment formation and transmission prior to 12 months. In this paper we lay out our recommendations for the study of the 4-month origins of disorganized attachment. In our subsequent Paper II we report on the results of a large empirical study that was conducted along the lines we recommend in Paper I. Both Papers I and II are based on Beebe, Jaffe, Markese, Buck, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 76 publications
0
45
0
5
Order By: Relevance
“…When interacting with their infants, autonomous parents are likely to show emotional acceptance and be skillful in supporting their infant's emotion regulation development. Parents with low sense of autonomy, in turn, can be fearful or intrusive in their interactions, forcing the infant to defensively regulate their own experiences and expressions (Beebe, Lachmann, Markese, & Bahrick, 2012;Lyons-Ruth, 1999). It is possible that the infant's early interpersonal strategies form the basis for later reliance on immature and neurotic defenses, involving distorted mental representations of self and others, and limited conscious awareness of one's own interpersonal needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When interacting with their infants, autonomous parents are likely to show emotional acceptance and be skillful in supporting their infant's emotion regulation development. Parents with low sense of autonomy, in turn, can be fearful or intrusive in their interactions, forcing the infant to defensively regulate their own experiences and expressions (Beebe, Lachmann, Markese, & Bahrick, 2012;Lyons-Ruth, 1999). It is possible that the infant's early interpersonal strategies form the basis for later reliance on immature and neurotic defenses, involving distorted mental representations of self and others, and limited conscious awareness of one's own interpersonal needs.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotic defenses, such as repression and reaction formation, are characterized by limited awareness of threat provoking thoughts and unacceptable emotions. Research suggests that early development of emotional self-awareness takes place within sensitive and well-attuned dyadic interactions, which provide the infant feedback about his/her own emotional states (Beebe et al, 2012;Gergely & Watson, 1996). In line with this, psychodynamic theory suggests that infants' symbolic representations of their own emotional needs are left "underdeveloped" with insensitive and rejecting caregivers, making them difficult to be consciously reflected later on (Lyons-Ruth, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Hannah's ability to convey to Peter that she understood what he was feeling through her touch, facial expressions, and the tone and rhythms of her voice, while maintaining enough distance to not become overwhelmed by it, helped Peter begin to regulate his affective states and form a secure attachment. Beebe et al's (2012) use of microanalysis of four-month, mother-infant, face-to-face communications to predict Mary Ainsworth's 12-month attachment classifications corroborates that it is the early dyadic, regulatory processes that establish attachment patterns. In Beebe's research (2010), specific patterns of mother and infant self-and interactive regulation are coded from splitscreen video recordings of the facial interactions and upper torso movements of both mother and baby.…”
mentioning
confidence: 57%
“…Beatrice Beebe (2010;Beebe et al, 2010;Beebe, Lachmann, Markese, & Bahrick, 2012) has demonstrated that babies' attachment classifications at one year can be predicted by the quality of the babies' and their mothers' vocal interaction patterns during face-to-face play when the baby is 4 months old. My close observations of Peter's and Hannah's interactions in the naturalistic setting of their home relate well to this finding.…”
mentioning
confidence: 99%
“…Ainsworth, 1969;Beebe y Lachmann, 1994, 2012Fonagy, Gyorgy, Jurist y Target, 2004;Hess y Main, 2000;Stolorow, 1997). Debido a que los patrones de apego y de regulación tempranos se hacen sentir a lo largo del tiempo incluso cuando se transforman, el bebé relacional permanece como una presencia viva en el espacio (adulto) de la consulta.…”
Section: Enactments En El Contexto Evolutivo: El Bebé Relacionalunclassified